Electrically tunable metasurfaces: from direct to indirect mechanisms. (1st July 2022) - Jeon, Nara; Noh, Jaebum; Jung, Chunghwan; Rho, Junsuk
Abstract: Intensive development of nanofabrication processes has opened a new window to control electromagnetic waves using subwavelength nanostructures array, named metasurfaces. Although the metasurfaces have succeeded in achieving unprecedented functionality by arranging various shapes of nanostructures to modulate the properties of the incident light, inherent passive characteristics make it impossible to alter the engraved functions after it is fabricated. To give tunability to metasurfaces, various methods have been proposed by using a thermal, chemical, optical and physical stimulus. In particular, electrically tunable metasurfaces are attractive in that they are easy to control precisely and could be integrated into electronic devices. In this review, we categorize the representative electrical tuning mechanisms and research into three; voltage-operated modulation, electrochemical-driven modulation, and externally mediated modulation. Voltage-operated modulation uses materials that could be directly reorganized by an electric field, including liquid crystals and Drude materials. Electrochemical-driven modulation adjusts the optical properties of metasurfaces through electrochemical responses such as electrochromism and electrodeposition. Lastly, externally mediated modulation causes a change in the geometric parameters of metasurfaces or in the phase of the constituent materials by converting electrical energy into thermal or mechanical stimulation. This paper concludes after explaining the pros and cons of each mechanism and the new possibilities which electrically-responsive metasurfaces could bring about.